Gestures in Prolonging Semantic Memory of Young EFL Learners: A Serial Retention - Nyak Mutia Ismail; Veni Nella Syahputri; Septhia Irnanda (Journal of Innovation in Educational and Cultural Research, 2022)
This study aimed at putting an experiment to young learners in acquiring through the use of gestures as the treatment process. This study was carried out under the procedure of the quasi-experimental approach with repeated measurement design. There were 35 primary school students involved in this study. The data were gathered through pretest-posttest. After the pretest was administered, the treatment process was carried out during the three following weeks by teaching the students verb vocabulary using gestures. The post-tests were then administered repeatedly in the 4th, 6th, and 7th week after the treatment to see the level of their memory retention. Later, the data obtained were analyzed using repeated test analysis. The results unveiled that the use of gestures can definitely enhance the students’ vocabulary intake. It implies that EFL teachers—especially those teaching youths—should consider integrating their teaching method with gestures, but they are expected to be more creative in generating understandable gestures to convey abstract verb vocabulary.